Anticancer potential of Tinospora cordifolia and arabinogalactan against benzo(a)pyrene induced pulmonary tumorigenesis: a study in relevance to various biomarkers - Vandana Mohan; Ashwani Koul (Shahrekord University of Medical Sciences, 2018)
Introduction: Aqueous Tinospora cordifolia stem extract (Aq.Tc) and arabinogalactan (AG), its bioactive polysaccharide, which are antioxidant remedies were evaluated on pulmonary cancer and associated tumor markers. Methods: Mice were randomly segregated into 6 groups. Group I: animals served as control. Group II: animals which were administered Aq.Tc extract (200 mg/kg, orally), thrice a week. Group III: animals which received AG (7.5 mg/kg, orally) thrice a week. Group IV: animals which were instilled with benzo(a)pyrene (B(a)P) (50 mg/kg, orally) twice within an interval of 2 weeks. Group V: animals which received Aq.Tc extract as in group II, along with B(a)P after 2 weeks of Aq.Tc administration. Group VI: animals which received AG as in group III along with B(a)P after 2 weeks of AG administration. Results: As expected, B(a)P treated mice exhibited high tumor incidence and multiplicity with concomitant increase in serum/plasma markers like carcinoembryonic antigen (CEA), circulating tumor DNA (ctDNA), lactate dehydrogenase (LDH) and tumor necrosis factor. However, Aq.Tc and AG supplementation to B(a)P abused animals significantly attenuated these parameters at different stages of cancer, depicting their anti-cancer effects in lung carcinogenesis. Also, treatment of Aq.Tc and AG to tumor bearing mice reduced the degree of histopathological alterations as compared to B(a)P installed mice. The apoptotic index in case of Aq.Tc and AG fed mice treated with B(a)P was higher as compared to only B(a)P treated mice. Further it was observed that Aq.Tc could induce higher degree of apoptosis when compared to AG group, suggesting Aq.Tc as a more effective modulator of tumorigenesis. Conclusion: Overall, these findings substantiate the chemopreventive potential of Aq.Tc and AG against lung tumorigenesis. Aq.Tc was found to be more effective than AG in modulating the process of lung carcinogenesis as reflected by various observations.